10p12.31-12.2 variants and risk of childhood acute lymphoblastic leukemia in a Chinese population. Issue 1 (January 2015) - Deng, Jianping; Xue, Yao; Wang, Yaping; Chen, Jing; Li, Jie; Lu, Qin; Wang, Meilin; Tong, Na; Zhang, Zhengdong; Fang, Yongjun
Abstract Acute lymphoblastic leukemia (ALL) is a clonal hematologic disease, and is the most common cause of childhood malignancy. Recently, a new locus was identified at 10p12.31-12.2 through a genome-wide association study (GWAS) that included racially and ethnically diverse populations. We conducted a replication study with 570 cases of ALL and 673 cancer-free controls to validated the association of this locus with ALL susceptibility in a Chinese population. The results of our study confirmed that the 10p12.31-12.2 locus was linked to childhood ALL susceptibility in the Chinese population. Interestingly, we also found that the single nucleotide polymorphisms (SNPs) in this locus had a larger effect on susceptibility to high-risk ALL than on susceptibility to low-risk ALL.